Dynamics of Coupled Structures, Volume 4 Proceedings of the 33rd IMAC, A Conference and Exposition on Structural Dynamics, 2015 - Allen, Matt.; Mayes, Randall L.; Rixen, Daniel J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Dynamics of Coupled Structures, Volume 4. Proceedings of the 33rd IMAC, A Conference and Exposition on Balancing Simulation and Testing, 2015, the fourth volume of ten from the Conference brings together  contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on:  Substructuring and the Ampair Wind Turbine Test Bed Experimental Dynamic Substructuring Reduced Order Models Experimental Studies of Joints and Joined Structures Analytical/Numerical Modeling of Joints Industrial Applications of Substructuring.
Robust Stability and Performance Analysis for Multi-Actuator Real-Time Hybrid Substructuring -- Effect of Actuator Delay on Real-Time Hybrid Simulation Involving Multiple Experimental Substructures -- Effective Control of a Six Degree of Freedom Shake Table -- Mathematical Equivalence Between Dynamic Substructuring and Feedback Control Theory -- Feasibility of a Transmission Simulator Technique for Dynamic Real Time Substructuring -- Ignoring Rotational DoFs in Decoupling Structures Connected Through Flexotorsional Joints -- A Comparison of two Component TPA Approaches for Steering Gear Noise Prediction -- Experimental Dynamic Substructuring of a Catalytic Converter System Using the Transmission Simulator Method -- A Modal Craig-Bampton Substructure for Experiments, Analysis, Control and Specifications -- A Comparison of the Dynamic Behavior of Three Sets of the Ampair 600 Wind Turbine -- Ampair 600 Wind Turbine 3-Bladed Assembly Substructuring Using the Transmission Simulator Method -- Quantifying Epistemic and Aleatoric Uncertainty in the Ampair 600 Wind Turbine -- A Craig-bampton Experimental Dynamic Substructure Using the Transmission Simulator Method -- A Parallel Solution Method for Structural Dynamics Response Analysis -- Structural Coupling Of Two-Nonlinear Structures.
Keywords: Mechanics; Mechanics, Applied; Buildings—Design and construction; Building; Construction; Engineering, Architectural; Engineering design; Solid Mechanics; Building Construction and Design; Engineering Design